(untitled) (Forum Penelitian Agro Ekonomi, 2023)
The Indonesian government has implemented a policy of exporting cocoa beans through the Minister of Finance Regulation No. 67/PMK.011/2010 to stimulate the growth of the processing industry. This article examines the policy’s effectiveness and impact on the cocoa industry. This study uses a literature review method from various secondary data sources. The results revealed that implementing the export duty policy had achieved its goal of developing the national cocoa industry and increasing exports. The policy impacts are the decline in cocoa bean exports, the growing cocoa processing industry, and the increase in processed cocoa exports. This policy raises side effects such as insufficient volume and quality of cocoa beans. The disconnect between upstream and downstream subsystems in cocoa agribusiness hinders the development of the national cocoa commodity. The government needs to carry out a few things for the cocoa industry. The government should implement a synergic and comprehensive policy alignment on the Indonesia cocoa agribusiness system, review the export duty rate policy to a flat 15%, improve productivity and increase cocoa bean production to compensate for the increased capacity of the cocoa processing industry. The government must also revitalize the national cocoa development movement by increasing cocoa competitiveness.